2001
DOI: 10.1007/bf02897952
|View full text |Cite
|
Sign up to set email alerts
|

ADL ability characteristics of partially dependent older people: Gender and age differences in ADL ability

Abstract: Age and gender differences in ADL ability were investigated using 568 Japanese partially dependent older people (PD, Mean age=82.2± ± ± ±7.76 years) living in welfare institutions. The subjects were asked about 17 ADL items representing 7 ADL domains by the professional staff working at subjects' institutions. Each item was assessed by a dichotomous scale of "possible" or "impossible". Item proportions of "possible" response were calculated for gender and age groups (60s, 70s, 80s and 90s). Two-way analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
3
12
0
Order By: Relevance
“…Namely, the ADL ability level and life satisfaction are suggested to be factors that bring about the decline in each other. In previous studies (Demura et al, 2000;Sato et al, 1999Sato et al, , 2001, the ADL ability of independent elderly was reported to decrease with aging. This tendency was also found in this study, and the decrease in the 80s group was extreme.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Namely, the ADL ability level and life satisfaction are suggested to be factors that bring about the decline in each other. In previous studies (Demura et al, 2000;Sato et al, 1999Sato et al, , 2001, the ADL ability of independent elderly was reported to decrease with aging. This tendency was also found in this study, and the decrease in the 80s group was extreme.…”
Section: Discussionmentioning
confidence: 89%
“…However, ADL consists of various activities, such as walking, dressing, eating, bathing, etc., and the pattern change with aging in these ability levels is not consistent among activities (Sato et al, 2001). In addition, the contribution to independent living is also different in each activity.…”
Section: Introductionmentioning
confidence: 97%
“…The reports in the literature regarding this vary considerably. Sato et al [ 44 ] reported no differences between the sexes with regard to performance for the 568 senior citizens they investigated. In the 90 elderly subjects studied by Bürge et al [ 45 ], the men achieved significantly better performances particularly in the domain of mobility, whereas, by contrast, the women had better results in the domains of hygiene and personal care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pattern in which disabilities occur over time within individuals was also examined, and this patter n dep endent on the difficu lty o f performing (Dunlop et al, 1999;Sato et al, 2001). The unidimensional ADL index assesses ADL ability with the hierarchical relationship in the scale (Spector et al, 1987).…”
Section: Discussionmentioning
confidence: 99%